Pengembangan Media Promosi Perumahan Berbasis Virtual Reality Mobile Dengan Reticle-Based Gaze Interaction - Daffa Atha Perdana; Tommy Bustomi; Farindika Metandi (Dinamik, 2026)
Conventional promotional media such as brochures, scale models, and two-dimensional images provide limited spatial exploration for prospective homebuyers. This study developed a mobile Virtual Reality application for housing promotion that integrates 360° panoramas, reticle-based gaze interaction, gyroscope orientation, a minimap, and interactive lighting and faucet controls. The application was developed using the Multimedia Development Life Cycle, comprising concept, design, material collecting, assembly, testing, and distribution. Interaction is performed through a raycast emitted from the center of the camera; an action is triggered after the reticle remains on a target for two seconds without an external controller. Android application functions were evaluated using Black Box Testing, while the visual effectiveness of the media was assessed with 36 respondents through a web-based panoramic tour using the EPIC Model. All functional scenarios were completed successfully. All questionnaire items were valid, with item correlations exceeding 0.329, and the Cronbach’s Alpha reliability value reached 0.917. The overall EPIC score was 4.37, categorized as Very Effective, with Impact obtaining the highest score of 4.41. These findings show that the 360° panoramic tour was effective as a visual promotional medium, while the reticle-based interaction mechanism in the Android application functioned as designed.